Advances in engineered T cell immunotherapy for autoimmune and other non-oncological diseases - Qiaolin Huang; Xiaojian Zhu; Yicheng Zhang (Biomarker Research)
Abstract Adoptive immunotherapy using engineered T cells expressing chimeric antigen receptors has shown remarkable success in treating patients with hematological malignancies. However, realizing broader therapeutic applications of engineered T cells in other diseases requires further exploration in clinical investigations. In this review, we highlight recent advances in the engineering of T cells in non-oncology areas, including autoimmune and inflammatory diseases, infections, fibrosis, hemophilia, and aging. Chimeric antigen receptor immunotherapy has shown good outcomes in non-oncology areas, but many challenges remain in improving its safety and efficacy and and expanding its application to the treatment of non-oncological diseases.